The closer the better? Relative influence of forest continuity and distance to water on the taxonomic and functional structure of riparian plant communities along headwater streams. Issue 2 (20th June 2021) - Janssen, Philippe; Chevalier, Richard; Evette, André; Archaux, Frédéric
Abstract: Questions: (a) Is forest temporal continuity an important factor in structuring the riparian plant communities along small alluvial valleys? (b) To what extent can distance from the stream modulate the effect of forest continuity and provide a better understanding of the taxonomic and functional structure of these communities? Location: Ouanne watershed, France. Methods: We used a paired‐samples design, involving stands close to and far from the stream, in ancient or recent riparian forests, in which we studied the vegetation. We performed analyses of species richness and cover, as well as mean values of species preferences and functional traits, and measures of species composition, distinguishing between the understorey and overstorey. Results: Strong differences in richness and mean values, as well as in composition, were found between ancient and recent forests. Ancient forests were characterized by species with a dominant stress‐tolerant strategy, whereas recent forests were dominated by hygrophilous and nitrophilous species with a dominant competitive strategy. Furthermore, we found that ancient and recent stands close to the stream encompassed a larger richness of species, than ancient and recent riparian stands far from the stream, a pattern mostly driven by the greater co‐occurrence of small ruderal species with rapid leaves turnover but also of ancient forest species. Conclusions: In small riparian forests along headwater streams, we have shown that past human activities leave still detectable traces in contemporary plant communities. In addition, we pointed out that colonization by ancient indicator species was faster in recent forests closer to the stream. This underscores the need to protect remaining ancient riparian forests that are well connected to the stream, even if they are small, and suggests that bank reforestation as well as restoration of hydrological connectivity on rivers fragmented by artificial barriers may be an effective way to increase forest biodiversity in riparian zones. Abstract : By studying plant communities in ancient and recent forests along headwater streams, we showed that past human activities left detectable traces even in small wooded patches. Specifically, we showed that proximity to the river increased stand colonization by ancient indicator species. This underscores the need to prioritize the conservation of ancient riparian forests that are well connected to the river.